Right Ventricular Function Predicts Clinical Response to Specific Vasodilator Therapy in Patients with Pulmonary Hypertension. Issue 1 (18th September 2012) - Giusca, Sorin; Jurcut, Ruxandra; Coman, Ioan Mircea; Ghiorghiu, Ioana; Catrina, Daniela; Popescu, Bogdan A.; Dima, Laura; Ginghina, Carmen
<x xml:space="preserve">Abstract</x> Introduction: We followed patients with pulmonary arterial hypertension (PAH) receiving specific vasodilator therapy and tested for predictors of clinical outcome. Methods: Thirty‐two patients (mean age 39 ± 15 years, 22 women, diagnosed with pulmonary hypertension; PH): 29 with PAH and 3 patients with inoperable chronic thromboembolic PH received therapy with either bosentan, sildenafil, or both and were evaluated with clinical parameters, biomarkers (B‐type natriuretic peptide values), and echocardiography before receiving specific medication and every 3 months thereafter. A right heart catheterization was performed at baseline. A composite endpoint of death, worsening of functional class, or the need of a second vasodilator agent was used to define the clinical nonresponders. Results: Patients were followed for 14 months (7.5–21). The endpoint was reached by 15 patients: four patients died (two idiopathic PAH and two PAH in context of Eisenmenger syndrome), seven patients showed 1 functional class worsening, and four patients needed to be switched to combination therapy. Patients who remained clinically stable or improved had at baseline a better cardiac output with a less remodeled right ventricle (RV) and better functioning RV (all P < 0.05). A RV fractional area change (RVFAC) lower than 25.7% and a RV global strain value higher than −13.4% predict with 87% sensitivity and 83% specificity (AUC 87.3%, P = 0.001) and 73% sensitivity and 91% specificity (AUC 84.2%, P = 0.003), respectively, patients who will deteriorate clinically under specific vasodilator therapy. A multivariate model showed RVFAC to be the only independent predictor of the endpoint with a HR of 0.87 (0.8–0.96), P = 0.007. Conclusions: Over an average period of 1 year, almost half of patients showed signs of clinical deterioration despite specific vasodilator therapy. Parameters of right ventricular morphology and function had prognostic value in these patients.